A New Model for Knowledge Management Implementation Process in Organizations . (Comprehensive Journal of Science, 2026)
The Knowledge Considering as one of the most important resources in any organizations nowadays, with all these cuts-throat competitions between organizations and dynamic changes, the organizations become thought-process oriented to enhance their performance and processes. In this respect, Knowledge Management (KM) processes have been turned nowadays into strategic resource for an organization at which KM is now perceived as a foundation of success or failure. In this paper describe main factors that impact on knowledge management implementation in the organization: these are organization, people and technology. We propose that there is a demand in every organization to reinforce the implementation efforts required for acquiring.
Keywords: Knowledge management, Knowledge Management Process, Technological Aspect.